2010
DOI: 10.1103/physrevb.82.064420
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and lattice dynamics of the magnetic shape-memory alloyCo2NiGa

Abstract: In addition to the prototypical Ni-Mn-based Heusler alloys, the Co-Ni-Ga systems have recently been suggested as another prospective materials class for magnetic shape-memory applications. We provide a characterization of the dynamical properties of this material and their relation to the electronic structure within a combined experimental and theoretical approach. This relies on inelastic neutron scattering to obtain the phonon dispersion while first-principles calculations provide the link between dynamical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 57 publications
6
26
3
Order By: Relevance
“…Overall, the lattice parameters and magnetic moments per Co atom obtained in these calculations are in good agreement with the previous calculations and experimental work. In agreement with previous theoretical studies 22,24 , the SPRKKR results suggest that the total magnetic moment increases upon tetragonal distortion. This observation is in agreement with general trends observed in experimental studies of Co-Ni-Ga alloys 42 .…”
Section: (B)supporting
confidence: 92%
See 2 more Smart Citations
“…Overall, the lattice parameters and magnetic moments per Co atom obtained in these calculations are in good agreement with the previous calculations and experimental work. In agreement with previous theoretical studies 22,24 , the SPRKKR results suggest that the total magnetic moment increases upon tetragonal distortion. This observation is in agreement with general trends observed in experimental studies of Co-Ni-Ga alloys 42 .…”
Section: (B)supporting
confidence: 92%
“…From electronic structure calculations, instability in Ni 2 MnGa is due to the lack of hybridization between 3d spin-down Mn and Ni states while in Co 2 NiGa, the instability is due to the location of the Fermi level at the beginning of low-lying spin-down antibonding states 22 . Similar theoretical work by Siewert et al 24 on Co-Ni-Ga Heusler alloys seems to corroborate the results presented in 22 , although in the former case the effect of disorder on the stability of the austenite phase was examined by exploring conventional Heusler L2 1 ordering as well as so-called inverse Heusler configurations in which one of the majority atoms-Co in this case-is replaced by either of the minority components-Ni or Ga in this instance.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…However, this cannot be generalized for all ternary alloys showing martensitic instabilities. For Co 2 NiGa, a newly found shape memory alloy, Siewart et al 35 observed that softening in TA 2 phonon branch was absent as a result of nonappearance of nesting features in the Fermi surfaces of Co 2 NiGa. Here, we present Fermi surfaces corresponding to the spin-minority bands only, since most prominent features are observed in this spin channel as the systems undergo martensitic transitions 19 .…”
Section: Inter-atomic Force Constantsmentioning
confidence: 99%
“…To be able to realize the advantages offered by these multi-functional materials in the automotive , aerospace and heavy machinery industries, there is a requirement for SMAs with much higher transformation temperatures. CoNiGa is one such promising shape memory alloy (SMA) which is the object of much interest due to it's potential as a magnetic SMA with a thermoelastic transition in the ferromagnetic state 1 . Cobalt has a large magnetic moment which ensures a high Curie temperature.…”
Section: Introductionmentioning
confidence: 99%